Cross‐Country Variability in Cost of Raising Equity: Evidence from Seasoned Equity Offerings. (30th May 2018) - Gupta, Manu; Prakash, Puneet; Rangan, Nanda K.
Abstract: We examine how county‐level governance affects the cost of raising equity. Using data on seasoned equity offerings, we find that the underwriting spread is determined by the litigation risk of issue certifiers, and offer underpricing is largely determined by the investment risk of the equity issue. Underwriting spread increases with enhanced legal enforcement, offsetting the reduction in underpricing associated with strong legal enforcement. Our study offers insight into the effect of legal enforcement and regulatory policy on the cost of raising equity.